PENERAPAN MODEL COOPERATIVE LEARNING TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN SIKAP DEMOKRASI DAN PRESTASI BELAJAR SISWA ( Pembelajaran pada PPKN Kelas XI SMAN 1 Gumay Talang ) - Diki Pusantra (DIADIK, 2020)
The purpose of this study was to determine: the application of the Two Stay Two Stray cooperative learning model (TSTS) in enhancing Democratic attitudes in PPKN Subjects in Class XI IPS , the application of the Two Stay Two Stray cooperative learning model (TSTS) can increase Student learning achievement in PPKN Subjects in Class XI IPS,) the application of the Two Stay Two Stray cooperative learning model (TSTS) to improve student learning achievement in PPKN Subjects in Class XI IPS. This research uses Classroom Action Research (CAR) and quasi-experimental designs. The subjects were 34 students of class XI IPS 2 semester 2. For the quasi-experimental sample of class XI IPS 1 students were 30 people and for the control class were class XI IPS3 as many as 30 people. Data collection techniques in this study used observation sheets and tests. The results showed that : the application of the Two Stay Two Stray learning model (TSTS), can improve students' democratic attitudes on PPKN subjects in Gumay Talang 1 High School in 2019/2020 Academic Year. the application of the Two Stay Two Stray learning model (TSTS), can improve student learning achievement and become a separate motivation for students to follow subject matter Two Stay Two Stray learning model (TSTS), effectively increasing student learning achievement in PPKN subjects